2013
DOI: 10.1093/mnras/sts695
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the H2-emitting gas in the Crab nebula★

Abstract: Understanding how molecules and dust might have formed within a rapidly expanding young supernova remnant is important because of the obvious application to vigorous supernova activity at very high redshift. In previous papers we have mapped the Crab Nebula in a roto-vibrational H 2 emission line, and then measured the molecular excitation temperature for a few of the brighter H 2 -emitting knots that we have found to be scattered throughout the Crab Nebula's filaments. We found that H 2 emission is often quit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(70 citation statements)
references
References 63 publications
5
65
0
Order By: Relevance
“…These enhanced values cover the limits estimated by Richardson et al (2013), based on the observed Crab synchrotron radiation and the degree of magnetic trapping. The grid was run using the UV and X-ray fluxes from the attenuated PWN spectrum described above.…”
Section: Reactionsupporting
confidence: 84%
See 4 more Smart Citations
“…These enhanced values cover the limits estimated by Richardson et al (2013), based on the observed Crab synchrotron radiation and the degree of magnetic trapping. The grid was run using the UV and X-ray fluxes from the attenuated PWN spectrum described above.…”
Section: Reactionsupporting
confidence: 84%
“…The rates for reactions 17 and 18 were taken from Shull & van Steenberg (1982) and from Kingdon & Ferland (1996), respectively. We also included reactions involving the H − anion from the UMIST database (McElroy et al 2013), to account for its role in the formation of H2 in the Crab Nebula (Richardson et al 2013). Electron impact excitation rates for the first six rotational levels of ArH + were taken from Hamilton et al (2016), and we used energy levels and Einstein A-coefficients from the Cologne Database for Molecular Spectroscopy (CDMS) (Müller et al 2001(Müller et al , 2005, in order to calculate the emissivity of ArH + rotational transitions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations